Respuesta :

Answer:

[tex]\boxed{\boxed{\sqrt[3]{d}\cdot \sqrt[3]{d}\cdot \sqrt[3]{d}=d}}[/tex]

Step-by-step explanation:

The given expression is,

[tex]=\sqrt[3]{d}\cdot \sqrt[3]{d}\cdot \sqrt[3]{d}[/tex]

It can also be written as,

[tex]=d^{\frac{1}{3}}\cdot d^{\frac{1}{3}}\cdot d^{\frac{1}{3}}[/tex]

The exponent product rule of algebra states that, while multiplying two powers that have the same base, the exponents can be added.

As here all the terms have same base i.e d, so applying the rule

[tex]=d^{\frac{1}{3}+\frac{1}{3}+\frac{1}{3}}[/tex]

[tex]=d^{\frac{1+1+1}{3}}[/tex]

[tex]=d^{\frac{3}{3}}[/tex]

[tex]=d^1[/tex]

[tex]=d[/tex]

Answer:

it's A

Step-by-step explanation:

i got it right on edge

ACCESS MORE